The Effectiveness of Developing Science Learning Devices with the Integrated PBL Model of the STEM Approach in Improving Students' Problem-Solving Ability and Self-Efficacy - Via Monica Devi; Susilawati; Kosim (Jurnal Penelitian Pendidikan IPA, 2024)
Natural science learning is a process of discovery, therefore science learning includes systematic exploration activities, which means not only mastering systematic accumulation but also the process of discovery. It's helps aid participants in solving problems. However, the phenomena encountered show that students' problem-solving abilities are still quite low. The low problem-solving ability is also influenced by students' self-efficacy. Therefore, it is necessary to innovate the development of science learning tools using appropriate models. One model that can be use is the integrated PBL model with the STEM approach. The development carried out aims to increase students' problem-solving abilities and self-efficacy. This type of research is R&D research with the ADDIE development model. Study findings indicate that students' problem-solving abilities have increased by 0.81 in the high category and their self-efficacy has increased by 0.30 in the medium category. These findings are based on the acquisition of the N-gain value. Consequently, it is beneficial to increase students' problem-solving skills and self-efficacy to design science learning resources that incorporate the PBL model and the STEM approach.